Essays on Philippine language and literature - Mabanglo, Ruth Elynia S; Galang, Rosita G. (Pasig City, 2010)
Any discussion of Filipino and Philippines literature would not be complete without an examination of issues surrounding their use and study in linguistics , cultural, political, socilogical , and educational contexts. The national language questions and the instructional medium dabate in the Philippines are only two of such issues which were discussed by writers, researcher, language teacher, and other scholars from different parts of the globe who attended the First International Conference o Filipino as a Global Language at the University of Hawai'i in March 2008. What was initially concieved as publications of the proceedings of the conference has been transformed to this collection of conference and other solicited papers organized into three sections: Philippine Literatur, Language and Polisy Issues, and Teaching and Research
Keywords: Filipino Language; Filipino Language- study and teaching; Philippine Literature